The increase of pavement cost due to the traffic overloads - Pais, Jorge C. (2017)
Publicado em "Bearing capacity of roads, railways and airfields: proceedings of the 10th International Conference on the Bearing Capacity of Roads, Railways and Airfields (BCRRA 2017)...". ISBN 978-1-138-29595-7